Association of Hepatitis B Virus Polymerase/Surface Gene Overlap Mutations Developed in Nucleos(t)id Analogue Treatments of Chronic Hepatitis B with Hepatocellular Carcinoma - Yeşim Saliha Gürbüz; Seda Erem Basmaz; Murat Sayan; Sadettin Hülagü (Düzce Tıp Fakültesi Dergisi)
Aim: Nucleos(t)id analogs (NA) used in hepatitis B virus (HBV) treatment may cause rtA181T and sW172* mutations. sW172* increases progression to hepatocellular carcinoma (HCC). This study aimed to reveal the rtA181T/sW172* mutation in HCC patients on the background of chronic hepatitis B (CHB) to determine its association with NA.Material and Methods: A total of 90 CHB patients, 42 patients with HCC (DNA of 4 patients could not be analyzed), and 48 patients without HCC as the control group, were included in this study. Patients in the control group were divided into two groups, those who received NA treatment (n=21) and those who did not (n=21). Drug resistance analysis was performed by DNA sequencing.Results: Among the 42 patients with HCC, the median age was 63 (range, 37-81) years, and the median HBV DNA level was 6.0x106 (range, 30-1.14x108) IU/ml. In the 48 patients included as controls, the median age and HBV DNA level were 46 (range, 20-75) years and 1.41x107 (range, 80-1.70x108) IU/ml in the treatment-naive patients, and 36 (range, 21-50) years and 7.6x106 (range, 15.9x102 - 5.1x107) IU/ml in the NA-treated patients, respectively. sW172* mutation, which causes rtA181T mutation to occur, was identified in only 2 (5.3%) patients in the study group with HCC.Conclusion: Association between HCC and rtA181T/sW172* mutation suggests that HCC may develop in patients under NA treatment. The rtA181T/sW172* mutation should be screened in patients receiving treatment, and when detected, they should be closely monitored for HCC development.